Euler-Type Integral Operator Involving S-Function - D. L. Suthar; Teklay Hailay (Abstract and Applied Analysis)
The object of the present paper is to establish some interested theorems on Euler-type integrals involving S-function, which is defined by Saxena and Daiya. Further, we reduce some special cases involving various known functions like the k-Mittag-Leffler function, K-function, and M-series.